Intracellular release of endocytosed nanoparticles upon a change of ligand-receptor interaction - Vácha, Robert; Martinez-Veracoechea, Francisco J; Frenkel, Daan (ACS nano, 2012)
During passive endocytosis, nanosized particles are initially encapsulated by a membrane separating it from the cytosol. Yet, in many applications the nanoparticles need to be in direct contact with the cytosol in order to be active. We report a simulation study that elucidates the physical mechanisms by which such nanoparticles can shed their bilayer coating. We find that nanoparticle release can be readily achieved by a pH-induced lowering of the attraction between nanoparticle and membrane only if the nanoparticle is either very small or nonspherical. Interestingly, we find that in the case of large spherical nanoparticles, the reduction of attraction needs to be accompanied by exerting an additional tension on the membrane (e.g., via nanoparticle expansion) to achieve release. We expect these findings will contribute to the rational design of drug delivery strategies via nanoparticles.
Keywords: Molecular Dynamics Simulation; molekulární konformace; velikost částic; Hydrogen-Ion Concentration; Solvents; Particle Size; Nanoparticles; vazba proteinů; fosfolipidy; simulace molekulární dynamiky; Intracellular Space; nanočástice; Molecular Conformation; Ligands; rozpouštědla; endocytóza; hydrofobní a hydrofilní interakce; Phospholipids; Endocytosis; Thermodynamics; intracelulární prostor; buněčná membrána; termodynamika; koncentrace vodíkových iontů; Protein Binding; ligandy; Cell Membrane; Hydrophobic and Hydrophilic Interactions